Competing Principles for Allocating Health Care Resources. Issue 5 (1st October 2016) - Carter, Drew; Gordon, Jason; Watt, Amber M.
Abstract: We clarify options for conceptualizing equity, or what we refer to as justice, in resource allocation. We do this by systematically differentiating, expounding, and then illustrating eight different substantive principles of justice. In doing this, we compare different meanings that can be attributed to "need" and "the capacity to benefit" (CTB). Our comparison is sharpened by two analytical tools. First, quantification helps to clarify the divergent consequences of allocations commended by competing principles. Second, a diagrammatic approach developed by economists Culyer and Wagstaff offers a visual and conceptual aid. Of the eight principles we illustrate, only two treat as relevant both a person's initial health state and a person's CTB per resource unit expended: (1) allocate resources so as to most closely equalize final health states and (2) allocate resources so as to equally restore health states to population norms. These allocative principles ought to be preferred to the alternatives if one deems relevant both a person's initial health state and a person's CTB per resource unit expended. Finally, we examine some possibilities for conceptualizing benefits as relative to how badly off someone is, extending Parfit's thought on Prioritarianism (a prioritizing of the worst off). Questions arise as to how much intervention effects accruing to the worse off count for more and how this changes with improving health. We explicate some recent efforts to answer these questions, including in Dutch and British government circles. These efforts can be viewed as efforts to operationalize need as an allocative principle. Each effort seeks to maximize in the aggregate quanta of effect that are differentially valued in favor of the worst off. In this respect, each effort constitutes one type of Prioritarianism, which Parfit failed to differentiate from other types.